EFEKTIVITAS ARBITRASE INTERNASIONAL DALAM PENYELESAIAN SENGKETA INVESTASI PASCA-ICSID: ANALISIS PERBANDINGAN ANTARA PENDEKATAN UNCITRAL DAN ICSID DALAM PERLINDUNGAN INVESTOR ASING - Gunawan Widjaja (INTELIGENSIA MEDIA, 2026)
This study aims to analyse the effectiveness of international arbitration in post-ICSID investment dispute resolution, focusing on a comparison between the UNCITRAL and ICSID approaches to the protection of foreign investors. The research method employed is a literature review (library research) using a normative-legal approach and comparative methods to identify the strengths and weaknesses of each arbitration mechanism. The results of the study indicate that ICSID offers greater certainty of enforcement through the self-contained enforcement mechanism under Article 54 of the ICSID Convention, which binds 160 contracting states to enforce awards without the intervention of national courts, whilst also providing a standardised institutional structure and the rarity of forum neutrality. However, ICSID faces serious criticism regarding high costs, lengthy durations, inconsistencies in awards, and potential interference with the host state’s regulatory space. Conversely, UNCITRAL offers greater procedural flexibility, lower costs, and higher transparency through the 2013 UNCITRAL Rules on Transparency; however, its main weakness lies in an enforcement mechanism reliant on the 1958 New York Convention, which requires the intervention of national courts and carries the risk of refusal of enforcement. From the perspective of foreign investors prioritising enforcement certainty, ICSID is superior, whilst from the perspective of transparency and cost efficiency, UNCITRAL is more competitive. Both mechanisms continue to adapt through the reforms of UNCITRAL Working Group III and the revision of the ICSID Rules 2022 to enhance effectiveness in the protection of foreign investors.